2021
DOI: 10.1111/1440-1630.12779
|View full text |Cite
|
Sign up to set email alerts
|

Stroke survivors' perspectives on recovering in rural and remote Australia: A systematic mixed studies review

Abstract: Introduction Stroke survivors recovering in rural and remote locations often have little or no access to rehabilitation services. The purpose of this study was to review the literature on recovering in rural and remote Australia, from the perspective of stroke survivors. Use of technology to support recovery was also explored. Methods A systematic mixed studies review was conducted and reported according to the ENTREQ and PRISMA statements. MEDLINE (Ovid), CINAHL (EBSCOhost), Scopus, PsycINFO (ProQuest), Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Based on participants in this study, access to health care for those stroke patients living in rural areas is still an issue. This finding also confirms a 2022 study that found stroke survivors in rural and remote areas want to live well, doing what matters to them, despite their challenges and possible isolation (S. M. Jackson et al, 2021). Young stroke survivors endorsed online service delivery as a preferred method to solve the unmet needs of living with stroke (Keating et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Based on participants in this study, access to health care for those stroke patients living in rural areas is still an issue. This finding also confirms a 2022 study that found stroke survivors in rural and remote areas want to live well, doing what matters to them, despite their challenges and possible isolation (S. M. Jackson et al, 2021). Young stroke survivors endorsed online service delivery as a preferred method to solve the unmet needs of living with stroke (Keating et al, 2021).…”
Section: Discussionsupporting
confidence: 80%
“…Both in the current findings and the existing literature, there remains a significant degree of hesitancy associated with receiving care outside of metropolitan locations, 30 often founded on the notion that services offered in rural sites will “fall short” compared to services offered in metropolitan facilities. 31 Despite this, most patients were ultimately satisfied with their care and transition outcomes after transitioning rural. This suggests that a vital part of improving equitable access to health care in non-metropolitan regions may start with taking steps to offset patient apprehension and hesitancy about transitioning rural.…”
Section: Discussionmentioning
confidence: 99%
“…The post-stroke dystonia is thought to result from Finally, DBS PLIC may act on nearby thalamic neurons, influencing thalamic reticular cells and/or modulating neuronal activity of thalamic relay cells to alter motor circuitry through thalamocortical signalling [7].…”
Section: Dbs In Dystonia and Motor Deficitsmentioning
confidence: 99%